1996
DOI: 10.1107/s0108270195015241
|View full text |Cite
|
Sign up to set email alerts
|

Ipriflavone, an Antiostheophorotic Agent

Abstract: The antiostheophorotic agent ipriflavone [7-(1-methyl-ethoxy)-3-phenyl-4H-1-benzopyran-4-one, C18H16O3] is an important member of the isoflavone family. The structure of the molecule is dominated by the dihedral angle (50 degrees) between the planes of the phenyl and benzo-pyran moieties. A structural comparison with other related published structures is represented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The somewhat lower values for II, by virtue of the possibility of a longer side chain may show a less flapping tendency(higher potential barrier to free rotation) than I. These dihedral angles are nevertheless, in the range observed in the previously determined isoflavone structures from 32° to 75° (LAKSHMI, KUMAR, SENTHILSELVAN & SUBRAMANIAN, 1996;SHOJA , 1992 a,b;BRETON, PRECIGOUX, COURSEILLE & HOSPITAL, 1975;KANEDA, IITAKA & SHIBATA, 1973;ACHARYA, PURANIK, TAVALE & ROW, 1986;BÖCSKEL, SIMON, VARGA & HERMECZ, 1996;MAZUREK et al, 1998). Despite the biochemical activity of flavones and isoflavones few are listed in the Cambridge data file.…”
Section: Resultsmentioning
confidence: 94%
“…The somewhat lower values for II, by virtue of the possibility of a longer side chain may show a less flapping tendency(higher potential barrier to free rotation) than I. These dihedral angles are nevertheless, in the range observed in the previously determined isoflavone structures from 32° to 75° (LAKSHMI, KUMAR, SENTHILSELVAN & SUBRAMANIAN, 1996;SHOJA , 1992 a,b;BRETON, PRECIGOUX, COURSEILLE & HOSPITAL, 1975;KANEDA, IITAKA & SHIBATA, 1973;ACHARYA, PURANIK, TAVALE & ROW, 1986;BÖCSKEL, SIMON, VARGA & HERMECZ, 1996;MAZUREK et al, 1998). Despite the biochemical activity of flavones and isoflavones few are listed in the Cambridge data file.…”
Section: Resultsmentioning
confidence: 94%
“…47 Analysis of the synthetic isoflavone, ipriflavone (7-isopropoxyisoflavone) which is used in the treatment of bone loss in osteoporosis, indicated that the molecular structure was dominated by the dihedral angle of 50 between the planes of the aryl and benzopyran moieties. 48 The synthesis of isoflavones can be broadly divided into three main synthetic pathways: the formylation of deoxybenzoins, the oxidative rearrangement of chalcones and flavanones, and the arylation of a preformed chromanone ring. Synthetic procedures using 2 -hydroxyphenyl benzyl ketones and 2 -hydroxychalcones have been reviewed.…”
Section: Isoflavonesmentioning
confidence: 99%
“…The ten atoms of the fused benzopyran ring system are approximately planar and inclined at 8.7(3)°to the aryl ring. In 6-hydroxyflavone 14 this angle is 9.8(2)°but in ipriflavone 15 it is closer to 50.0°. The torsion angle C2 -C1 -C12 -C17 is 8.9(8)°and the C1 -C12 bond length here is 1.457( 7) Å.…”
Section: X-ray Crystallographymentioning
confidence: 89%